Leiomyoma of the female urethra: A rare presentation of a common tumour in a uncommon site - Nabaneet Majumder; V. Dafle; S. Patil (Journal of the Scientific Society, 2014)
Leiomyoma of the female urethra is a rare benign neoplasm arising from the smooth muscles. Here, we report a case of 60 year old female patient presented with pain in the abdomen and dysuria for 2 months. On cystoscopy, external urethral meatus normal. A large, non-pedunculated tumor arising from left lateral wall of urethra extending from bladder neck up to the proximal end of the external urethral meatus. The mass was excised and submitted for histopathological examination. Histology reveals leiomyoma.